THE CONCEPT OF THE CULTURALLY RESPONSIVE TEACHING IN EDUCATION (Web of Teachers: Inderscience Research, 2024)
Culturally responsive teaching is an educational approach that considers the different cultural backgrounds of students. Within the paradigm of modern education, CRT has emerged as a crucial strategy to promote inclusivity, equity, and academic achievement for students from diverse cultural and linguistic backgrounds. This article discusses the core principles of CRT, its theoretical underpinning, practical enactments across diverse classrooms, and its implications for student outcomes.